The gluten enteropathy in East Slovakia - Harvanová, Gabriela; Duranková, Silvia; Csanády, Alexander (Alergologia Polska - Polish Journal of Allergology, 2021)
Celiac disease is characterized as an autoimune disorder, and the trigger is gluten delivered into the body in a meal. The main purpose of the study was the issues about gluten enteropaty in East Slovakia, based on special scientific and foreign literature which was avaliable, also there are characteristics about digestion, celiac disease and gluten, critical factors and also premiss beginners of celiac disease. The research, which is discussed at the end of the thesis, was conducted in East Slovakia, namely in the gastroenterologic ambulance in the Humenné town. The above-mentioned research brought us information about the current position of celiac disease between different ages in the Humenné region. Our main aim was to find out whether there is any significant correlation between the age and risk of involvement of celiac disease.